Fluctuations in Direct Investment in Indonesia - Mohamad Taufik (Muhammadiyah University Press, 2014)
This study aims to analyze the effect of interest rate, Gross Domestid Product (GDP) per capita, exchange rate Rupiah to U.S., net export, tax rate, tax incentives (tax allowances), and ease of service and licensing to FDI in Indonesia during the period 1985-2011. The analysis model used in this study is a multiple regression model of time series data so will know the factors affecting FDI in Indonesia during the period 1985-2011. The result shows that variable interest rate, GDP per capita, exchange rate Rupiah to U.S., tax rate, tax incentives (tax allowances), and ease of service and licensing have a significant effect on the entry of FDI in Indonesia, but the net export variable have not a significant effect on the entry FDI.